Occidentalism and the techno-scientific coloniality - Jochum, Georg (2017)
This article interprets the coloniality of power as a synthesis of the eurocentric submission of the world and the anthropocentric domination of nature. The coloniality of modernity, which was established with the conquest of America, was expanded and transited to a project of the colonization of nature. Occidentalism thus became a project of technical progress. At present, this program undergoes an radicalization due to the spread of a ‘coloniality of technoscience’, based on an cybernetic thinking. Finally in the article will be presented new perspectives of epistemological decolonization by a critique of techno-scientific epistemology.